Some Effects of Unemployment on the Health of Unemployed Quebec Workers - Soderstrom, Lee (Relations industrielles / Industrial Relations, 1988)
The author estimates the effect of being unemployed on the health of unemployed Quebec workers. The results imply that the health effects are heterogenous, at least for unemployed men and women.